The UN Convention on the Rights of Persons with Disabilities A Commentary (Oxford Oxford University Press, 2018)
This treatise is a detailed article-by-article examination of the United Nations Convention on the Rights of Persons with Disabilities (CRPD). Each article of the CRPD contains a methodical analysis of the preparatory works, followed by an exhaustive examination of the contents of each article based on case law and concluding observations from the CRPD Committee, judgments from national and international courts and tribunals, pertinent UN and other reports, and literature on the topic in question. Although primarily addressed to lawyers, the volume features commentary from a broad range of scholars across a variety of disciplines in order to provide a comprehensive study of the legal, psychological, education, sociological, and other aspects of the CPRD. This encyclopaedic commentary on the CRPD effectively covers all the issues arising from international disability law and practice.
English
Keywords: Disability & the law; un convention; persons with disabilities; rights; CRPD